2015
DOI: 10.1002/tal.1262
|View full text |Cite
|
Sign up to set email alerts
|

Detail design, building and commissioning of tall building structural models for experimental shaking table tests

Abstract: SUMMARYIn the areas of seismic engineering, shaking table tests are powerful methods for assessing the seismic capacity of buildings. Since the size and capacity of existing shaking tables are limited, using scale structural models seems to be necessary. In recent years, many experimental studies have been performed using shaking table tests to determine seismic response of structural models subjected to various earthquake records. However, none of the past research works discussed practical procedure for crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Based on similarity law, the hybrid structure, whose main materials are microconcrete with cubic compressive strength of 8.1 MPa, 14 and 20 iron wires, and red copper, is designed according to seismic intensity fortification 7 . The 7° frequent/basic/rare earthquake means that the exceeding probability in the design period of 50 years equals to 63%/10%/2–3%, respectively.…”
Section: Shaking Table Testmentioning
confidence: 99%
“…Based on similarity law, the hybrid structure, whose main materials are microconcrete with cubic compressive strength of 8.1 MPa, 14 and 20 iron wires, and red copper, is designed according to seismic intensity fortification 7 . The 7° frequent/basic/rare earthquake means that the exceeding probability in the design period of 50 years equals to 63%/10%/2–3%, respectively.…”
Section: Shaking Table Testmentioning
confidence: 99%
“…Therefore, there is a strong engineering motivation for a site-dependent dynamic response analysis for many foundations in order to determine the free-field earthquake motions. Recent studies [1][2][3][4] have revealed that the performance level of steel unbraced frames is very sensitive to lateral deformations and drifts. Performance levels describe the states of structures after being subjected to a certain hazard level and are classified as: fully operational, operational, life safe, near collapse, or collapse [5].…”
Section: Introductionmentioning
confidence: 99%
“…Shaking table test is an effective approach to investigate the seismic behavior and failure mechanism of structures . It is widely used for the irregular structures, such as complex supertall buildings and multitower connected structures, which are not currently included in the design codes.…”
Section: Introductionmentioning
confidence: 99%